Social Identity and Fans' Behavior among European Soccer Club Supporters in Ibadan, Nigeria - Tegbe Ebenezer Adekola; Ashafa Bolanle (Universitas Medan Area, 2025)
This study investigates the impact of European football league viewership on the formation of social identity among fans of different football clubs in Ibadan, Nigeria, with a focus on how this identity formation influences patterns of social interaction. Guided by Social Identity Theory, the study examines the cognitive processes involved in how individuals incorporate football club affiliations into their self-concept. The research adopted a quantitative method with a descriptive survey design. A total of 100 young male adults, selected using a stratified purposive sampling technique from five soccer viewing centers in the Oluyole Local Government Area of Ibadan, participated in the study. Data was collected using questionnaires and analyzed using descriptive statistics (frequency counts and percentages). Findings indicate that the UEFA Champions League significantly influences the development of social identity among young male fans, with club loyalty shaping interpersonal relationships, fostering strong in-group camaraderie, and occasionally contributing to intergroup tensions. The study concludes that the social identities formed through football fandom extend beyond viewing centers to influence broader social behaviors and interactions in everyday life.